Hubungan Umur dan Lingkar Pinggang Dengan Kadar Trigliserida pada Peserta Prolanis di Puskesmas Sumbang I - Wahyu Dwi Asriani; Umi Solikhah; Supriyadi Supriyadi; Retno Sulistiyowati (CV. Ulil Albab Corp, 2022)
A decline in physical functional health and the tendency of morbidity increase in the elderly. One of which is coronary heart disease and one of the risk factors is hypercholesterolemia. Waist size is strongly correlated with central obesity and cardiovascular risk. In this case, cardiovascular disease ranks as the first cause of death in Indonesia. It is a general term that describes diseases of the heart or blood vessels. Excess levels of triglycerides in the body are called hypertriglyceridemia. The study was conducted in April-May 2022 by doing descriptive observation. There were only respondents out of 87 were analyzed using univariate and then by correlation test with the result that there is no relationship between age and triglyceride levels with Sig value. F Change (P) of 0.235, which means the value is > 0.05. In the results between waist circumference and triglyceride levels, the results of Sig. F Change (P) of 0.002 which means the value is <0.05 so it can be concluded that waist circumference with triglyceride levels has a relationship and has a strong relationship level at the R value (Correlation Coefficient) of 0.617 has a strong relationshi.